Induction of Ferroptosis by Ophiopogonin-B Through Regulating the Gene Signature AURKA in NSCLC - Li, Liqiu; Gao, Qian; Wang, Jin; Gu, Ling; Li, Zhihui; Zhang, Shiping; Hu, Cheng; He, Menglin; Wang, Yulin; Wang, Zixuan; Yi, Yongxiang; Fu, Jin; et al. (Frontiers in Oncology, 2022)
Ferroptosis is a new type of iron-dependent programmed cell death. In recent years, its role in the diagnosis and treatment of multiple tumors, including non-small cell lung cancer (NSCLC), has been uninterruptedly found. The relationship between ferroptosis-related genes and the prognosis of NSCLC patients needs to be clarified. In this study, Cancer Genome Atlas (TCGA) and the Gene Expression Synthesis Database (GEO) were used to build a model of ferroptosis-related differentially expressed genes (DEGs). 101 ferroptosis-related DEGs were screened by R language, and the12-gene signature was finally established through univariate Cox regression analysis and lasso-penalized Cox regression analysis. According to the risk score, patients were divided into a high-risk or low-risk group, and patients in the low-risk group had a better prognosis. AURKA, one of the 12 gene signatures, was found to be highly expressed in tumors. In addition, further study verified AURKA to be a negative regulator of ferroptosis in NSCLC cells. Ophiopogonin-B (OP-B) had been reported to induce apoptosis, mitotic catastrophe, autophagy in NSCLC cells. Herein, proteomic sequencing analysis and OP-B administration showed the up-regulation of AURKA and down-regulation of PHKG2 and SLC7A5 in the 12-gene signature, indicating that OP-B induced NSCLC ferroptosis. Determination of malondialdehyde (MDA), glutathione (GSH), intracellular iron concentration, and mitochondrial membrane potential (MMP) confirmed the induction of ferroptosis by OP-B in vitro. And transmission electron microscopic (TEM) examination of lung cancer xenotransplantation in nude mice also confirmed that OP-B induced ferroptosis in vivo. Further study of the molecular mechanism showed that the ferroptosis effect caused by OP-B could be partially reversed by AURKA overexpression. Overall, our study established a new ferroptosis-related risk prediction model for the NSCLC patients’ prognosis, revealed the enrichment pathways of ferroptosis in NSCLC, and discovered the negative regulation of AURKA on ferroptosis. On this basis, we proclaimed that OP-B could induce ferroptosis in NSCLC, and clarified the specific molecular mechanism of OP-B inducing ferroptosis by regulating the expression of AURKA.